2010
DOI: 10.1016/j.cbi.2010.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical mechanism of Caffeic Acid Phenylethyl Ester (CAPE) selective toxicity towards melanoma cell lines

Abstract: In the current work, we investigated the in-vitro biochemical mechanism of caffeic acid phenylethyl ester (CAPE) toxicity and eight hydroxycinnamic/caffeic acid derivatives in-vitro, using tyrosinase enzyme as a molecular target in human SK-MEL-28 melanoma cells. Enzymatic reaction models using tyrosinase/O2 and HRP/H2O2 were used to delineate the role of one- and two-electron oxidation. Ascorbic acid (AA), NADH and GSH depletion were used as markers of quinone formation and oxidative stress in CAPE induced to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 41 publications
1
41
0
2
Order By: Relevance
“…In addition, CAPE (2) showed a radiosensitization effect on A549 lung cancer cells, which suggested the possibility that treatment with CAPE (2) can result in enhancement of local control of lung cancer by radiotherapy without normal lung damage in vivo (Chen et al, 2004). Other studies have demonstrated that CAPE (2) not only showed itself as a strong activator of ROS generation possibly due to GSH depletion and reduction of mitochondrial membrane potential, but also had a radiosensitizing capability for IR co-treatment through inhibition of IR-induced NF-κB activation, resulting in sensitivity to IR and enhanced IR-induced apoptosis in several cancer cells (Chen et al, 2005;Lee et al, 2008;Kudugunti et al, 2010).…”
Section: Radiosensitizing Effects Of Phenylpropanoids Caffeic Acid Phmentioning
confidence: 99%
“…In addition, CAPE (2) showed a radiosensitization effect on A549 lung cancer cells, which suggested the possibility that treatment with CAPE (2) can result in enhancement of local control of lung cancer by radiotherapy without normal lung damage in vivo (Chen et al, 2004). Other studies have demonstrated that CAPE (2) not only showed itself as a strong activator of ROS generation possibly due to GSH depletion and reduction of mitochondrial membrane potential, but also had a radiosensitizing capability for IR co-treatment through inhibition of IR-induced NF-κB activation, resulting in sensitivity to IR and enhanced IR-induced apoptosis in several cancer cells (Chen et al, 2005;Lee et al, 2008;Kudugunti et al, 2010).…”
Section: Radiosensitizing Effects Of Phenylpropanoids Caffeic Acid Phmentioning
confidence: 99%
“…A gradual dosage-dependent inhibition of cell proliferation was observed upon 6 days treatment with compound 1 . Then DNA damage by compound 1 in the B16-F1 cells was characterized through alkaline comet assay3536. For negative control experiment, HeLa cells were used and nearly no DNA damage was observed in the even treated with higher concentrations of compound 1 (SI Figure S16a–f), which supported the tyrosinase-stimulated cross-linking mechanism in vivo .…”
Section: Resultsmentioning
confidence: 74%
“…The usefulness of propolis in therapy of neoplastic diseases is connected predominantly with its ability to induce apoptosis and anti-proliferative activities. In numerous in vitro research, propolis exhibited proapoptotic activities on various types of neoplastic cells such as in the cases of: laryngeal cancer, lung carcinoma, pancreatic cancer, thyroid neoplasm, colorectal cancer, breast cancer, prostate cancer and malignant glioma [24,25].…”
mentioning
confidence: 99%